2014
DOI: 10.1177/0960327114542883
|View full text |Cite
|
Sign up to set email alerts
|

Testicular development of male mice offsprings exposed to acrylamide and alcohol during the gestation and lactation period

Abstract: Acrylamide (Ac) in the foods and alcohol (Al) in the drinks are unavoidable. Several previous studies demonstrated that these substances which are taken into the body via diet may cause adverse effects in the cells. However, there is no study about how Ac and Al may affect the male reproductive system of the offspring when consumed by the mother during pregnancy and lactation. For this purpose, sexual development in male mice was evaluated after intake of 14 mg/kg Ac and 2 g/kg Al from gestation day 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The authors found that acrylamide and alcohol caused the formation of multinuclear giant cells and degeneration of tubules and maturation-arrested tubules, as well as a reduction in the number of spermatic, Sertoli, and Leydig cells. In addition, lipid peroxidation levels and superoxide dismutase enzyme activity were raised following treatment with acrylamide and alcohol [35]. Similar findings have been observed in human studies [36][37][38][39][40][41] reporting that alcohol might impair male fertility by damaging the anterior pituitary gland, causing the alteration of two fundamental hormones for reproductive function, luteinizing hormone (LH) and follicle-stimulating hormone (FSH), and by interfering with hormone production in the hypothalamus.…”
Section: Alcoholsupporting
confidence: 80%
See 1 more Smart Citation
“…The authors found that acrylamide and alcohol caused the formation of multinuclear giant cells and degeneration of tubules and maturation-arrested tubules, as well as a reduction in the number of spermatic, Sertoli, and Leydig cells. In addition, lipid peroxidation levels and superoxide dismutase enzyme activity were raised following treatment with acrylamide and alcohol [35]. Similar findings have been observed in human studies [36][37][38][39][40][41] reporting that alcohol might impair male fertility by damaging the anterior pituitary gland, causing the alteration of two fundamental hormones for reproductive function, luteinizing hormone (LH) and follicle-stimulating hormone (FSH), and by interfering with hormone production in the hypothalamus.…”
Section: Alcoholsupporting
confidence: 80%
“…Hence, it was hypothesised that the increased testicular impairment is directly associated with day-by-day alcohol consumption. Sen and co-authors [35] analysed the effect that acrylamide in food and alcohol might cause on cell development of the male mouse reproductive system when ingested by the mother during pregnancy and lactation. The authors found that acrylamide and alcohol caused the formation of multinuclear giant cells and degeneration of tubules and maturation-arrested tubules, as well as a reduction in the number of spermatic, Sertoli, and Leydig cells.…”
Section: Alcoholmentioning
confidence: 99%
“…In a study, the researchers administered 5,10,15 mg kg −1 bw −1 AA for 8 weeks to male adult rats and established that AA decreased testosterone and TAS levels in testis tissues, increased MDA levels and caused spermatogonia degenerations based on the dose (Hamdy, Bakeer, Eskander, & Sayed, ). In another study, the researchers administered 14 mg kg −1 bw −1 AA between the 6th day of the pregnancy until birth (21st day) and examined the testis tissue of male rat offspring, and concluded that AA increased lipid peroxidation and caused connective tissue deformation, atrophic tubule and multinuclear giant cell (Şen, Tunali, & Erkan, ). 11‐week male rats were administered 30 mg kg −1 bw −1 AA and 70 mg kg −1 bw −1 green tea for 3 weeks and established that AA lowered testosterone hormone levels compared to the control group; however, green tea administration prevented the adverse effects of AA such as the thickening of the tubular endothelium and the degeneration caused in the germ cells (Yassa, George, Refaiy, Effat, & Moneim, ).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these different outcomes are difficult to determine, but the time window of ethanol exposure may be a critical factor. Various preclinical models of FASD focus on distinct periods of development that may differentially affect brain processes and circuits (for review, see Marquardt & Brigman, 2016; Mooney & Varlinskaya, 2011), testis morphology, and testosterone levels (Lan, Vogl, & Weinberg, 2013; Şen, Tunali, & Erkan, 2015). Despite the possibility that distinct outcomes are associated with the extension of ethanol exposure to the early postnatal period, the effects of ethanol exposure that is restricted to this period of development on aggressive behavior have not been sufficiently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Social dominance, using the tube dominance test, was also studied since previous findings demonstrated that a tendency toward aggression can affect social interactions (Wang et al., 2011). Moreover, testis structure and testosterone levels of male mice were evaluated because testosterone is known to play a key role in aggressiveness and because early ethanol exposure can lead to gonadal alterations later in life (Lugo et al., 2006; Şen et al., 2015).…”
Section: Introductionmentioning
confidence: 99%